2008
DOI: 10.1121/1.2839000
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic energy harvesting using an electromechanical Helmholtz resonator

Abstract: This paper presents the development of an acoustic energy harvester using an electromechanical Helmholtz resonator (EMHR). The EMHR consists of an orifice, cavity, and a piezoelectric diaphragm. Acoustic energy is converted to mechanical energy when sound incident on the orifice generates an oscillatory pressure in the cavity, which in turns causes the vibration of the diaphragm. The conversion of acoustic energy to electrical energy is achieved via piezoelectric transduction in the diaphragm of the EMHR. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 24 publications
0
79
1
Order By: Relevance
“…It generated an open circuit voltage of 15mV pp under the airflow of 1.6kPa. Liu et al (2008) demonstrated the development of an acoustic energy harvester using Helmholtz resonator. It uses a piezoelectric diaphragm to extract energy.…”
Section: Examplesmentioning
confidence: 99%
“…It generated an open circuit voltage of 15mV pp under the airflow of 1.6kPa. Liu et al (2008) demonstrated the development of an acoustic energy harvester using Helmholtz resonator. It uses a piezoelectric diaphragm to extract energy.…”
Section: Examplesmentioning
confidence: 99%
“…Acoustic energy harvesting performs conversion of acoustic energy into electrical energy by using piezoelectric transduction [54]. Piezoelectric and electromagnetic based acoustic energy harvesters are developed [55].…”
Section: Acousticmentioning
confidence: 99%
“…Yet, little effort has been given to exploit the energy of traveling waves in fluids and structures. Only a few research groups have studied this area with a focus on polarization-patterned piezoelectric solids [17], quarter-wavelength resonators [18], Helmholtz resonators [19][20] and phononic crystals [21][22][23][24]. In addition, Yang et al [25] combined the sonic crystal concept with the Helmholtz resonators to enhance the acoustic energy harvesting.…”
Section: Introductionmentioning
confidence: 97%